The Analgesic Effect of Oxygen in Suspected Acute Myocardial Infarction: A Substudy of the DETO2X-AMI Trial - Sparv, David; Hofmann, Robin; Gunnarsson, Annika; James, Stefan; Hedberg, Camilla; Lauermann, Jörg; Torild, Petronella; Omerovic, Elmir; Bergström, Kristina; Haugen, Espen; Bergström, Camilla; Linder, Rikard; et al. (JACC. Cardiovascular interventions, 2018)
In this substudy of the DETO2X-AMI (An Efficacy and Outcome Study of Supplemental Oxygen Treatment in Patients With Suspected Myocardial Infarction) trial, the authors aimed to assess the analgesic effect of moderate-flow oxygen supplementation in patients with suspected acute myocardial infarction (AMI) treated with percutaneous coronary intervention (PCI) and to study the effect of oxygen supplementation on the use of opiates and sedatives during PCI. Routine oxygen in normoxemic patients with AMI does not provide clinical benefit. However, oxygen may relieve ischemic pain. Patients were randomly allocated to oxygen or ambient air according to the main study protocol. After PCI, peak level of pain during PCI was measured by the Visual Analogue Scale. The total amount of opiates and sedatives was reported. A total of 622 patients were enrolled: 330 in the oxygen group and 292 in the ambient air group. There was no significant difference in peak level of pain (oxygen 4.0 [1.0 to 6.0] vs. air 3.0 [0.6 to 6.0]; p = 0.37), use of opiates (mg) (oxygen 0.0 [0.0 to 3.0] vs. air 0.0 [0.0 to 3.0]; p = 0.31), or use of sedatives between the groups (median [interquartile range]) (oxygen 2.5 [0.0 to 2.5] vs. air 2.5 [0.0 to 2.5]; p = 0.74). In the present study, the authors did not find any analgesic effect of routine oxygen as compared with ambient air, and no differences in the use of sedatives and opiates during PCI. Our results indicate that moderate-flow oxygen supplementation does not relieve pain in normoxemic patients with suspected AMI undergoing treatment with PCI and should thus not be used for this purpose.